Competing Concepts of Inequality in the Globalization Debate - Ravallion, Martin (World Bank, Washington, D.C., 2013)
Differing value judgments in measuring inequality underlie the conflicting factual claims about how much poor people have shared in the economic gains from globalization. Opponents in the debate differ in the extent to which they care about relative inequality versus absolute inequality, vertical inequalities versus horizontal inequalities, and whether they are consistently individualistic in assessing the extent of inequality. The value judgments on these issues made by both sides need greater scrutiny if the globalization debate is to move forward.